Bladder Stones Removal Surgery Using Cystotomy in a Mix Breed Cat: A Case Report - Antika, Dona Dwi; Kartanegara, Aulia Azka Suradi; Rickyawan, Nofan (Universitas Airlangga, 2021)
Urolithiasis is a common disease affecting the urinary tract, including the bladder. This disease characterized by the presence of stones in the urinary tract. Urolithiasis is caused by a build up of mineral crystals. A two-year-old female mixed breed cat with a body weight of 2 kg was brought to the Ontosenovet clinic, Malang City with complaints of anorexia, oligouria, stranguria, and hematuria. The results of physical examination found that the cat was lethargy, 6% dehydrated and at the time of urination the urine was hematuria. The supporting examination is carried out in the form of ultrasound examination (USG). The results of ultrasound examination showed a hyperechoic colored foreign object with an oval shape with smooth edges at the base of the bladder which was suspected to be calculi and resulted in acoustic shadowing at the bottom of the calculi. The cat is diagnosed with urolithiasis with the prognosis of fausta. The procedure is performed is a cystotomy to take calculi in the bladder. Postoperative therapy is marbofloxacin antibiotic injection therapy (SC) 2 mg/kg BW and dexamethasone anti-inflammatory injection therapy (SC) 0.2 ml/cat. Therapy was continued with the administration of the oral antibiotic amoxicillin 25 mg/kg BW, metronidazole antibiotic 15 mg/kg BW, and dexamethasone 0.5 mg/kg BW as an anti-inflammatory. The cat experienced changes after surgery and was given therapy for five days marked by smooth urination without hematuria and no pain at the time of urination.